Pengungkapan Akuntansi Sumber Daya Manusia: Pengujian Peran Diversifikasi, Kepemilikan Asing, Listing Age, dan Leverage pada Perbankan - Darma, Sherry Margaretiya M.; Rokhmania, Nur'aini; Diptyana, Pepie (Politeknik Negeri Samarinda, 2024)
This study aims to examine the effect of product diversification, foreign ownership, listing age, and leverage on human resource accounting disclosure. This study uses secondary data obtained from annual reports and financial reports from all banks listed on the Indonesia Stock Exchange in 2020-2022. The samples in this study used purposive sampling method so that 135 samples were obtained. The analytical method used in this research is multiple linear regression. The results of this study indicate that diversification product have an effect on human resource accounting disclosure. Meanwhile, foreign ownership, listing age, and leverage have no effect on human resource accounting disclosure.